2000
DOI: 10.1124/mol.57.4.718
|View full text |Cite
|
Sign up to set email alerts
|

Hexapeptide and Cyclic Pentapeptide Endothelin Antagonists Directly Activate Pituitary Gonadotropin-Releasing Hormone Receptors

Abstract: In the course of our studies toward the development of novel analogs of the decapeptide gonadotropin releasing hormone (GnRH), we have examined a hexapeptide that is an antagonist of endothelin (ET). It was found that this peptide, Ac-D-Trp-LeuAsp-Ile-Ile-Trp (peptide 1), binds specifically to the pituitary GnRH receptor. Moreover, peptide 1 exhibits a GnRH agonistic activity (i.e., it induces luteinizing hormone release from rat pituitary). This activity is mediated directly by the GnRH receptor and is suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Nevertheless, we have previously demonstrated that peptide I can activate the pituitary GnRH receptor and induce LH secretion. 6 Peptide I, derived from the sequence of the C-terminal domain of ET, binds specifically to pituitary GnRH receptors with a moderate affinity (K i ) 1.9 µM), whereas ET itself does not bind to the GnRH receptor. 6 We have also found that removal of the acetyl group of the peptide I results in a hexapeptide (D-Trp-Leu-Asp-Ile-Ile-Trp, peptide II) (Table 1) with similar properties with respect to the GnRH receptor, but with a diminished affinity toward the ET receptor.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, we have previously demonstrated that peptide I can activate the pituitary GnRH receptor and induce LH secretion. 6 Peptide I, derived from the sequence of the C-terminal domain of ET, binds specifically to pituitary GnRH receptors with a moderate affinity (K i ) 1.9 µM), whereas ET itself does not bind to the GnRH receptor. 6 We have also found that removal of the acetyl group of the peptide I results in a hexapeptide (D-Trp-Leu-Asp-Ile-Ile-Trp, peptide II) (Table 1) with similar properties with respect to the GnRH receptor, but with a diminished affinity toward the ET receptor.…”
Section: Introductionmentioning
confidence: 99%
“…41 Furthermore, cyclic tetrapeptides have been found that inhibit histone deacetylases, 42 and cyclic pentapeptide antagonsists have been discovered for endothelin. 43 Considering their high affinity, target specificity, and metabolic stability, it seems likely that cyclic peptides will continue to gain attention as powerful biological tools.…”
mentioning
confidence: 99%